Perancangan Sistem Pemantau Ruangan pada Perangkat Bergerak - Kusuma, Darmawan Surya; Sudjadi, Sudjadi; Isnanto, R. Rizal (Transmisi, 2012)
The monitoring system continued to evolve along with technological advances. This system aims to find information about the status of a particular object, as an evaluation material of the object. The development also occurs in mobile technology. Nowadays, mobile devices can be customized according to user needs. By looking at both development of technologies, there should be a development of monitoring system using mobile devices so the users can get the ease of doing monitoring process for a specific object whenever and wherever by using the application in theirs mobile device. This project is divided into four step. The first step is conduct an analysis of the methods that’s to be used in this research. The second step is designing an UML (Unified Modeling Language) to realize this system. The third step is creating and compiling the application program. Application programs is created using Java2 Micro Edition programming language (J2ME) on the Blackberry development environment. The final step is perform a tests on this application. Based on the results of tests performed, can be concluded that with these mobile applications, the users can perform a monitoring activities such as set the monitoring camera to take a pictures and access the server to request a monitoring pictures. As a monitoring system, this application provides direct monitoring (live) and the monitoring of time on request (on demand) and also provides the configuration screen for setting the monitoring time, interval cameras capture speed, interval slideshow, connection mode, the server's IP, and server port. The tests performed on Blackberry device. Keywords : Monitoring system, mobile device, UML (Unified Modeling Language), Java2 Micro Edition programming language (J2ME), Blackberry development environment, Blackberry device.